(untitled) (Medico Legal Update, 2021)
This study aimed to Modify the PEEK surface using Fractional CO2 laser in different range of parameters to change the surface topography regarding roughness and wettability to enhance osseointegration. A PEEK block (Ceramill PEEK 98X20 N -JUVORA dental innovations, UK) was used to prepare substrate. By CADCAM system, PEEK was cut into discs (2 mm thickness and 10 mm diameter). the discs were smoothed by silicon carbide paper of 500 grit and a rotation motion, polishing machine at 200 rpm for one minute used to polish the discs, finally cleaned with ethanol alcohol using ultrasonic cleaner. Different parameters were tested to study their effects on PEEK surface; therefore, several trails were done using Fractional CO2 laser device. Surfaces of the irradiated PEEK discs were examined microscopically at different magnification power. Then SEM was used. Then, PEEK samples were scanned by (EDS). Range of powers were used (2, 4, 6, 8, 10, 12) W The distance between spots was 0.2mm and 0.2 ms pulse duration to ensure maximum coverage of laser effect. The energy range was (4 - 25) which was n’t enough to produce any effect. To test the effect of pulse duration different values were also studied starting from 0.2ms then increase the pulse duration. 0.4,0.6,0.8 ms to increase the energy per pulse accordingly. Starting from short pulse duration up to 0.6ms there was no effect even when the power increased. At 0.8 ms pulse duration, the effect was recognized on the specimen surface. The collected data of previous trials direct the operator to reduce pulse duration to have best criteria, including surface roughness, wettability, without carbonization or cracks. Conclusions: Successful modification of PEEK surface can be done with fractional CO2 laser. Laser parameters as power, pulse duration, distance between spotes and number of scans are key factors induced different range of effect considering material’s properties.